The management of setting out in construction - Smith, James R. 1935- (ICE design and practice guide., 1997)
Discusses the advantages and pitfalls of the increasing use of global positioning systems instruments in providing control for projects, and how this revolutionises the way in which setting out is performed in the future. This work is suitable for engineers and surveyors involved in the planning, design, and execution of a construction project.